Comparison of non‐burn‐specific systemic inflammatory response syndrome criteria and burn‐specific American Burn Association systemic inflammatory response syndrome criteria in paediatric burned patients. (25th August 2020) - Dalgic, Nazan; Sahin, Ayse; Karadag, Cetin A; Sancar, Mesut
Abstract : Aim: We aim to investigate the diagnostic value of newly defined criteria for the systemic inflammatory response syndrome (SIRS) for paediatric burn patients by the American Burn Association (ABA) by comparing the non‐burn‐specific SIRS criteria for children. Methods: A total of 147 paediatric burn patients were included in this study. Patients diagnosed with sepsis were included in the sepsis group. Clinical parameters were obtained from the electronic medical records at the time of preliminary sepsis diagnosis. Both the non‐burn‐specific SIRS criteria and the burn‐specific ABA SIRS criteria were applied to both the sepsis group and the non‐sepsis group. Results: Of 147 patients, 50 had sepsis according to the non‐burn‐specific sepsis criteria. When the 50‐patient sepsis group was compared to the 97‐patient non‐sepsis group, the sepsis group had a significantly higher duration of hospitalisation, burn percentage, burn state and abbreviated burn scoring index (ABSI) ( P < 0.05). The specificity of the two scales was 29.9% for the non‐burn‐specific SIRS and 74.2% for the burn‐specific ABA SIRS. The sensitivity for the burn‐specific ABA SIRS was calculated as 58%, the sensitivity for the non‐burn‐specific SIRS was 100%. While positive predictive value was calculated as 42.4% for the non‐burn‐specific SIRS, this value was found as 53.7% for the burn‐specific ABA SIRS criteria. The correlation coefficient between the non‐burn‐specific SIRS and the burn‐specific ABA SIRS was 0.378 ( P < 0.001). Conclusions: Our study underlines the need for widespread use of more specific and sensitive burn‐specific clinical criteria to early diagnosis of infection in burn patients to prevent unnecessary antibiotic usage.